Species-Area Relationships in the Tropical Deciduous Forests of Jharia Coalfield, India - Mishra, Shruti; Anshumali (Indian Forester, 2015)
Species-area relationships (SARs) were characterized the spatial distributions of legumes and nonlegumes in three sites of the tropical deciduous forests around Jharia Coalfield (JCF) in the eastern part of India. Three 1 ha plots were established one in each site, located 6 to 20 km apart. Each plot was divided into 100 quadrats each of 10 m Ã— 10 m in size. The observed species-area curves were initially steep followed by gradual species accumulation, but none of the sites did the curve reach an asymptote. These curves were best fitted by the power model due to low P value 2 (probability under the null hypothesis), high F ratio (regression mean square over the error mean square) and high Ra (adjusted coefficient of determination) indicating 1 ha sampling plots were intermediate in size in three sites. In this study, the Z-value decreased with increase in C-value indicating both were simply fitted constant and independent of biotic and abiotic characteristics of the sampling sites. The species-area relationships showed distinct habitat heterogeneity and dispersal limitation for "all species, legumes and nonlegumes" in the tropical deciduous forests.